THE THOUGHT OF FIGURES OF ISLAMIC MASS ORGANIZATION ABOUT CALIPHATE: A CASE STUDY IN BANDA ACEH AND WEST JAVA - Wajdi Ibrahim, Farid; Wirianto, Dicky; Adib, Shohibul (Islam Futura, 2022)
This article aims to address the questions related to the support and rejection of figures of Islamic mass organizations to the concept of the caliphate. Some of the previous literature limited the object to the behavior of the Muslim community towards the ideology of the caliphate in the historical context and its relation to the modern state, neglecting the source of inspiration for the caliphate ideology as understood and perceived by figures of mass organization Indonesia. Therefore, using a phenomenological approach, the researchers attempt to fill the gap in this particular issue. This research was conducted in two cities in Indonesia, Aceh and West Java. This form of field study takes a phenomenological approach and thus is exploratory. Interviews and documentation have been used to collect data. This research found three main tendencies of Islamic mass organizations in Aceh and West Java in understanding the concept of the caliphate, textualist-substantive, contextualist-substantive, and ideological-political. Textualist-functionalists see the Islamic caliphate as mandatory, without having to change the ideology or identity of a country. Contextualist-Substantive argues that the Khilafah is a value that does not contradict with Pancasila's state ideology. Ideological and political Islamists believe that the fight to establish an Islamic State, or Daulah Islamiyyah Khilafah, is a necessity and even an obligation.